The Confederations Cup in the coverage by Folha de São Paulo: power relationships, conflicts and interests in the media - Ivan Daniel Müller; Janaina Andretta Dieder; Gustavo Roese Sanfelice (Acta Scientiarum. Human and Social Sciences, 2018)
The present article aims at analyzing and interpreting the coverage by Folha de São Paulo concerning the social demonstrations which took place in Brazil in June, 2013, related to the Confederations Cup/Brazil/2013. The qualitative/descriptive corpus-based research focused on the articles posted on the newspaper Folha de São Paulo from June 7th, 2013 to July 2nd, 2013, a period of time which was followed by and included the 2013 FIFA Confederations Cup, comprising the Social Demonstrations that occurred in June, 2013, in Brazil. By applying Goffman’s frame analysis (2004), we have chosen the following categories: ‘Folha de São Paulo’s vandals!?’; ‘Violence and police abuse making the headlines’; ‘Redefining the frames: highlights in the political domain’. We have come to the conclusion the Folha de São Paulo was concise when highlighting in its frames the public expenditure on non-priority projects, actual legacies and the intransigencies placed on the requirements that FIFA imposed to Brazil.